Bad Company and Burnt Powder : Justice and Injustice in the Old Southwest - Alexander, Bob, 1943- (Book collections on Project MUSE., 2014)
Bad Company and Burnt Powder is a collection of twelve stories of when things turned ""Western"" in the nineteenth-century Southwest. Each chapter deals with a different character or episode in the Wild West involving various lawmen, Texas Rangers, outlaws, feudists, vigilantes, lawyers, and judges.